Time-Dependent Antibacterial Effects of Citrullus Colocynthis Seed Extract Compared to Calcium Hydroxide in Teeth Infected with Enterococcus Faecalis - Yasamin Ghahramani; Najmeh Mohammadi; Saman Baghaei; Negar Ghorbani Jahandizi (Shiraz University of Medical Sciences, 2024)
Statement of the Problem: Endodontic efforts are focused on eliminating intracanal pathogens. Applying intracanal medicament for infected teeth is beneficial for achieving better antibacterial effects in endodontic treatments. Different intracanal medicaments should be assessed and compared for this purpose.Purpose: to assess the antibacterial efficacy of Citrullus colocynthis seed extract comparing to Ca(OH)2 on teeth contaminated with Enterococcus faecalis.Materials and Method: In this in vitro study, a novel strain of Enterococcus faecalis (Enterococcus spp. ATCC 19433) yielded from the root canal treated tooth with persistent apical periodontitis. The canals of 78 human single-rooted extracted teeth were contaminated with mentioned strain and treated with Citrullus colocynthis essential oil and Ca(OH)2 for 1, 7, and 14 days. To determine the chemical composition of the oils, gas chromatography-mass spectrometry (GC-MS) was applied. The percentage reduction from baseline c.f.u./mL values was estimated.Results: Oleic acid, benzoic acid, and gallic acid were the major contents of Citrullus colocynthis essential oil. The c.f.u./mL count decreased considerably as contact duration rose for both medicaments. After 7 days, a statistically significant difference was identified between the medicaments. Citrullus colocynthis showed higher antimicrobial efficacy. However, after 14 days, no substantial difference was found.Conclusion: Citrullus colocynthis essential oil, displayed great antimicrobial efficacy against Enterococcus faecalis higher than Ca(OH)2 over the first week contact period.